Transient nature of the employees' job satisfaction: The case of the IT industry in Bosnia and Herzegovina - Muamer Bezdrob; Aziz Šunje (European Research on Management and Business Economics (ERMBE), 2021)
In a time of persistent and fierce "war for talents," which is naturally inherent to the knowledge-intensive industries, the issue of employees' job satisfaction is of the utmost managerial significance. In that respect, this study explores certain intrinsic factors that underlie the job satisfaction concept, as well as the durability of employees' job satisfaction. Based on the extant literature, a theoretical model of job satisfaction was designed, which was subsequently tested using the data gathered through the surveys conducted over the ten years. The results obtained by model testing show that employees' job expectations make up that particular intrinsic factor that differentiates job satisfaction from non-satisfaction. More intriguingly, the results showed that prior job satisfaction is not a reliable predictor of later job satisfaction.
Keywords: J28; M54; 650; Job satisfaction; Intrinsic factors; Job expectations; IT industry